Combination Adaptive Traffic Algorithm and Coordinated Sleeping in Wireless Sensor Network - Al Rasyid, M. Udin Harun; Aji, Eka Saputra; Nadhori, Isbat Uzzin (Politeknik Elektronika Negeri Surabaya (PENS), 2014)
Wireless sensor network (WSN) uses a battery as its primary power source, so that WSN will be limited to battery power for long operations. The WSN should be able to save the energy consumption in order to operate in a long time.WSN has the potential to be the future of wireless communications solutions. WSN are small but has a variety of functions that can help human life. WSN has the wide variety of sensors and can communicate quickly making it easier for people to obtain information accurately and quickly. In this study, we combine adaptive traffic algorithms and coordinated sleeping as powerâ€efficient WSN solution. We compared the performance of our proposed ideas combination adaptive traffic and coordinated sleeping algorithm with nonâ€adaptive scheme. From the simulation results, our proposed idea has goodâ€quality data transmission and more efficient in energy consumption, but it has higher delay than that of nonâ€adaptive scheme.Keywords:WSN,adaptive traffic,coordinated sleeping,beacon order,superframe order.